Analisis Halal Supply Chain Management Produk Kosmetik Halal Terhadap Tingkat Kepuasan Remaja Di Kota Medan - Raudah Azzahra Manurung; Vina Rahmanda; Siti Aisyah (LPPM Universitas Labuhanbatu, 2022)
Halal Supply Chain Management is halal management activities in storage, procurement, transportation, handling, shipping, inventory management, and other corporate governance strategies such as lean and value-based management. Consumer satisfaction is the level of consumer sentiment after comparing what he received with his expectations. The purpose of this study is to determine the halal supply chain management on the satisfaction level of halal cosmetic products. This study uses a descriptive method, a questionnaire distribution method with intentional simplification, a quantitative survey approach using criteria for adolescents aged 19-24 years with a sample of 100 people, and a test tool using SPSS 25. The results of this study explain when halal supply chain managementl (X) increases , the level of satisfaction (Y) also increases, and conversely, when the halal supply chain managementl (X) decreases, the level of satisfaction (Y) also decreases..